MONITORING OF THE ENVIRONMENTAL STATE OF THE RIVERS OF THE CHECHEN REPUBLIC - M. Sh. Saidova; Kh. N. Askhabova; M. S. Ozdikhanov; K. A-V. Shuaipov (Юг России: экология, развитие)
The ecological status of the river Argun and Squirrel. It is shown that the Argun River and Squirrel are classified as "moderately polluted" water quality class III. The basic measures to protect water resources from pollutants CR.